Challenges of leadership in modern organizations: knowledge, vision, values - CHIRIMBU, Sebastian (Annals of Spiru Haret University. Economic Series, 2014)
The article highlights the issue of leadership in the context of the exercise in the knowledge-based organization. Connections between organizational culture, management culture and leadership in modern organizations highlight the manner in which leadership is exercised in the context of knowledge of the organization's foundation. Leadership means knowledge and practice, it means quality. Organizations need managers, but they also need leaders. It is desirable for the two areas to overlap in the largest possible extent. Modern approaches emphasize the evolution of these relations to the area where the legitimacy of the leadership's concern is justified by the development and promotion of other leaders.